2014
DOI: 10.1371/journal.pone.0099849
|View full text |Cite
|
Sign up to set email alerts
|

Notoginsenoside R1 Attenuates Atherosclerotic Lesions in ApoE Deficient Mouse Model

Abstract: AimsAtherosclerosis is the primary cause of cardiovascular diseases and stroke. The current study evaluated the interventional effects of a naturally occurring compound Notoginsenoside R1 (NR1) on atherosclerosis in ApoE−/− mice.Methods and ResultsThe atherosclerotic lesion was significantly alleviated by NR1 treatment and this attenuation was marked by reduction in lipid deposition, fibrosis and oxidative stress. Increased serum levels of GSH and SOD and decreased level of MDH were observed in NR1-treated Apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 35 publications
4
36
0
Order By: Relevance
“…With the development of pharmacology, a variety of monomer saponins have been identified, including ginsenoside Rb1, ginsenoside Rg1 and notoginsenoside R1 (NGR1). In regard of AS, a previous study has reported NGR1 as a promising anti-AS agent by modulation of inflammation, oxidative stress, lipid metabolism and the expression of miRNAs [13]. However, the detailed function of NGR1 on AS, and the possibly underlying mechanisms still need to be revealed.…”
Section: Introductionmentioning
confidence: 98%
“…With the development of pharmacology, a variety of monomer saponins have been identified, including ginsenoside Rb1, ginsenoside Rg1 and notoginsenoside R1 (NGR1). In regard of AS, a previous study has reported NGR1 as a promising anti-AS agent by modulation of inflammation, oxidative stress, lipid metabolism and the expression of miRNAs [13]. However, the detailed function of NGR1 on AS, and the possibly underlying mechanisms still need to be revealed.…”
Section: Introductionmentioning
confidence: 98%
“…It have been reported that NR1 has antioxidant effects both in vivo and in vitro [39,40]. In this study, we also demonstrated that NR1 reduced oxidative stress both in serum and kidney cortex from STZ-induced diabetic rats.…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with previous reports [37,38], the present study showed increased MDA content and decreased activities of CAT and SOD and GPx in STZ-induced diabetic rats. More recently, NR1 has been found to have antioxidant effects both in vivo and in vitro [39,40]. In this study, the serum and tissue activities of antioxidant enzymes (CAT, SOD and GPx) were significantly increased and the MDA content decreased in NR1-treated rats, suggesting a significant antioxidant effect of NR1.…”
Section: Discussionsupporting
confidence: 57%
“…It has been reported that PPARγ agonist could block classical activation of macrophages and attenuates inflammation in diabetic atherosclerosis, thus may promote a more favourable plaque morphology 43, 44. In addition, atherosclerosis is also affected by lipid profiles and glucose metabolism 45, 46. There was a trend towards a decrease in blood glucose levels in the 20(S)‐Rg3–treated diabetic mice, which might also contribute to its anti‐atherosclerotic effects 47…”
Section: Discussionmentioning
confidence: 99%